Litter Treatment with Aluminum Sulfate (Alum) Produced an Inconsistent Reduction in Horizontal Transmission of Campylobacter in Chickens - Arsi, K.; Moore Jr., P.A.; Donoghue, A.M.; Dirain, M.L.; Donoghue , D.J. (International Journal of Poultry Science, 2017)
Background and Objective: Campylobacteriosis is a significant health problem worldwide and poultry are considered as one of the main vehicles of transmission. This study was conducted to determine whether alum reduces Campylobacter colonization in broilers by reducing horizontal transmission between birds or by reducing Campylobacter counts in birds already colonized (Therapeutic efficacy). Materials and Methods: Two replicate experiments were conducted and in each experiment, day of hatch broiler chicks (n = 295) were divided into 7 treatment groups including controls. Each treatment was reared in either no (0 kg), low (0.78 kg m–2) or high (1.58 kg m–2) concentrations of aluminum sulfate (alum; Al+ Clear). During days 7, 14, 28 and 42, ten birds from each treatment were analyzed for Campylobacter counts in the ceca. To evaluate whether alum inhibits horizontal transmission between birds, Campylobacter negative birds were reared with seeder birds that served as carriers. Results: Alum reduced (p